2002
DOI: 10.1002/jsfa.1204
|View full text |Cite
|
Sign up to set email alerts
|

Protein nutritive quality during production and storage of dietetic biscuits

Abstract: A comparative investigation of the changes in available lysine content during industrial production of two dietetic hard biscuits based on whole grain wheat flour/grits and a standard hard biscuit based on white wheat flour was performed. Dough preparation did not significantly affect the available lysine content. However, after baking, a significant loss (27-47%) of available lysine was found in all three types of biscuit. The average relative decrease in available lysine in proteins of each type of biscuit c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…It is probable that there was substantial loss of reactive lysine during baking because of the Maillard reaction, which was enhanced by the lysine contributed by the soy proteins. Similar losses (27–47%) were noted during the production of dietetic biscuits (Horvatic & Eres, 2006).…”
Section: Resultssupporting
confidence: 73%
“…It is probable that there was substantial loss of reactive lysine during baking because of the Maillard reaction, which was enhanced by the lysine contributed by the soy proteins. Similar losses (27–47%) were noted during the production of dietetic biscuits (Horvatic & Eres, 2006).…”
Section: Resultssupporting
confidence: 73%
“…Overall, the cookies had the largest reduction in total lysine for all of the sorghum types. The presence of sugar and high temperature during baking resulted in the loss of lysine because of the Maillard reaction . Serrem et al found similar reduction in lysine upon baking of sorghum cookies and attributed this loss to the Maillard reaction.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably due to the severity of the heat treatment reducing the IVPD considerably and also the reduction in lysine due to Maillard reactions especially for the cookies (34). …”
Section: Resultsmentioning
confidence: 99%
“…During the last decades, the mineral and protein concentrations of annual wheat cultivars have shown a continuous decline coinciding with the significantly increased grain yield (Fan et al, 2008). Common wheat cultivars are known to be low in content of some essential amino acids, especially lysine and threonine, the two most deficient amino acids (Abdel-Aal and Sosulski, 2001;Horvatić and Ereš, 2002). An effective method to counteract micronutrient malnutrition is to exploit the genetic variation of overall micronutrient availability in the wild wheat relatives and develop cultivars with enhanced nutritional values (Monasterio and Graham, 2000;Murphy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%